The Role of Financial Literacy in Improving Financial Inclusion Through The Use of E-Wallets Among Generation Z in Cirebon - Nadia Sylviani; Ario Purdianto (Greenation Research & Yayasan Global Resarch National, 2026)
This study is motivated by the limited number of studies examining the role of e-wallets as a mediator between financial literacy and financial inclusion, particularly among Generation Z in Indonesia. The purpose of this study is to analyze the influence of financial literacy on improving financial inclusion through the use of e-wallets among Generation Z in the city of Cirebon. This associative quantitative research uses primary data collected through an online questionnaire distributed to 150 Generation Z respondents (aged 15–29 years) in Cirebon who have used e-wallet services. Data analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) indicates that financial literacy has a positive and significant direct effect on financial inclusion, as well as an indirect effect through increased use of e-wallets. These findings demonstrate that e-wallets function as an effective mediating variable, indicating that strengthening financial literacy can encourage the adoption of digital financial services and ultimately expand financial inclusion among the younger generation.